14.0k views
2 votes
How can I do substitution method in Algebra 2? The equations are y= x^2-2x-3 and y=x^2+5x+11

User Dayvon
by
4.9k points

1 Answer

0 votes


\bf \begin{cases} \boxed{y} = x^2-2x-3\\ y = x^2+5x+11 \end{cases}\qquad\qquad \stackrel{\textit{substituting on the 2nd equation}}{\boxed{x^2-2x-3} = x^2+5x+11} \\\\\\ ~~\begin{matrix} x^2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~ -2x-3= ~~\begin{matrix} x^2 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~ +5x+11\implies -2x-3=5x+11\implies -3=7x+11 \\\\\\ -14=7x\implies \cfrac{-14}{7}=x\implies \blacktriangleright -2=x \blacktriangleleft


\bf \stackrel{\textit{since we know that }y = x^2-2x-3}{y=(-2)^2-2(-2)-3} \implies y = 4+4-3\implies \blacktriangleright y = 5 \blacktriangleleft \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill (-2,5)~\hfill

User CBaker
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.